THE EFFECT OF ELLIPSE-CIRCULAR GRANULAR RATIO TO INTRUDER RISING TIME ON TWO-DIMENSIONAL BRAZIL NUT EFFECT - Zacky Fairuza, Achmad
Granular material is a collection of macroscopic, discrete solid objects in very large quantities. The Brazil-nut Effect is one of the unique phenomena that occurs in granular material. Brazil-nut effect phenomenon is the event when grains that having larger size than the surrounding (intruder) is rising to the top of the granular beds when given a vibration in the vertical direction. The study entitled The Effect of Ellipse-Circular Granular Ratio to Intruder Rising Time on Two-Dimensional Brazil Nut Effect was motivated by various studies related to granular bed shape, especially ellipses. This study aims to understand the effect of ratio in the mixture of elliptical and circlular grains in the case of the Brazil-nut effect. The test was carried out using the 2-dimensional method and digital image processing. The ratio of the mixture and amplitudes are varied to observe the intruder rising time. The initial position of the intruder is also varied to see the grain movement. The results obtained from this study indicate the ratio of the mixture affect the rise time of intruder. A mixture of 80-90% bed circle towards ellipse gives the smallest rising time value. Furthemore, greater the amplitude value also increases the grain rise time. The ratio of elliptical and circle mixture also increases the degree of porosity in the initial arrangement of the grains. The trajectory of the intruder is affected by the slant of the experiment system, so intruder movement will tend towards to the edge of the container.